STUDI BRAND POSITIONING TOKO KOPI KEKINIAN DI INDONESIA - Linda Wijaya; Layinuvar Anggia Rizka (Eqien - Jurnal Ekonomi dan Bisnis, 2021)
The new concept coffee shop was born in Indonesia in 2017 and known as coffee shop kekinian. This coffee shop kekinian is growing in every corner of the capital, especially big cities in Indonesia by presenting almost the same concept, namely ready-to-go coffee shop, providing a menu of palm sugar milk coffee as the main menu and a new price range of IDR 15,000 - IDR 28,000. The development of this coffee shop is also because consumers are generation Y and Z consumers and the growth of female consumers as new coffee drinkers. With the massiveness of the current coffee shop competition, it has almost the same coffee shop characteristics in terms of menu, price range, consumer, marketing strategy. The author conducted a study on the positioning of 3 coffee shops kekinian that have the most store locations, namely Kenangan Coffee, Janji Jiwa Coffee, and Kulo Coffee. Research was conducted on generations Y and Z using narrative qualitative methods to get deeper insights from consumers and to find out whether consumers know the differences between the three coffee shops. The results of this research indicate that there is a similarity or as a point of parity, namely palm sugar ice milk coffee, is the most favorite flavor, promotion through digital, social media affects the desire to buy, purchasing directly in stores or via online applications is something that is often done, the necessity to share on social media after buying contemporary coffee is also done as a way to show that you are following current trends, women as a potential target market for coffee kekinian. Besides, these three coffees kekinian have differences, which are the points of difference, namely : Kenangan coffee described as romantic and millenial coffee, Janji Jiwa coffee described as wise and mature coffee. Kulo coffee described as fun coffee , coffee for millenial. Several factors to make the success of a contemporary coffee shop, namely having a clear positioning and having a good quality taste, and following a marketing strategy that follows the trend.